Between Democratic Modernization and Authoritarian Punitiveness in Brazil: Mass Incarceration, Political Rationalities and the Dynamics of Subnational Variation - Fonseca, David S. (The British journal of criminology, 2024)
Since the return to democracy in the 1980s, the Federal government in Brazil promoted the democratic modernization of the criminal justice apparatus. However, the arrival of a post-neoliberal government to the federal administration at the beginning of the century took place simultaneously with the emergence of mass incarceration. Rather than readily blaming their penal policies for this development, the present work addresses aspects of subnational variation and different political rationalities for comprehending this increase in the prison population. The coexistence of neoliberal and post-neoliberal rationalities of governance around the country between 2007 and 2018 corresponded to significantly diverse trends in incarceration at the state level, in which neoliberal governments played a more prominent role. Besides, authoritarian punitiveness has acted as an obstacle to the modernization of crime and punishment practices and institutions throughout this period. The resurgence of authoritarianism as an autonomous political rationality in the 2018 elections reconfigured policies and attitudes in the field, mostly by reversing past modernizing efforts.